A Module-Based Pediatric ECG Curriculum to Improving Accuracy of ECG Interpretation by Pediatric Emergency Medicine Providers - Priya Gopwani; Shilpa Patel; E. Anne Greene; Jennifer Chapman (Association of American Medical Colleges, 2014)
Abstract Introduction Electrocardiograms (ECGs) are ordered frequently in the pediatric emergency department (ED). The majority of these ECGs are interpreted initially by pediatric emergency medicine (PEM) physicians, with a cardiologist reinterpreting the ECG after patient disposition has been made. Previous studies have shown that neither emergency medicine nor pediatric residency training programs adequately train residents to read ECGs. We designed a web-based pediatric ECG curriculum aimed specifically at fellow and attending PEM providers. The overall goal of this curriculum is to improve the "first read" accuracy of ECG interpretation and decrease the number of missed diagnoses. Methods The curriculum consists of seven web-based modules focusing on pediatric ECGs and their interpretation in the ED setting. These modules cover the basics of pediatric ECGs, long QT syndrome & brugada, supraventricular tachycardia and Wolff Parkinson White syndrome, heart block and sick sinus syndrome, ventricular tachycardia, ischemia and infarct, and congenital heart disease. The case-based modules run for 7-12 minutes and are interactive, requiring the user to recognize abnormalities and perform necessary calculations before proceeding. Results This module was administered to PEM fellows at a large urban pediatric teaching hospital. A pretest consisting of 20 ECGs was administered to all PEM fellows and a self-selected group of PEM attendings. At the completion of the curriculum, a posttest was administered to assess improvement. The average accuracy of identifying the ECG abnormality at pretest was 42.8% (PEM Fellows M = 40.6%, N = 9; PEM Attendings M = 45.7% N = 7). All nine fellows completed the posttest. There was a statistically significant improvement in the PEM fellows' ability to accurately interpret ECG findings using these modules were used (42.0% v 53.1%, p = .047, Wilcoxon Signed-Rank test). On an accompanying satisfaction survey, 100% would recommend the curriculum to a colleague and 76.5% thought the ECG modules could stand alone in teaching ECG interpretation to PEM providers. Discussion There is a need to improve the ability of PEM physicians to read ECGs, particularly those with clinically significant findings. We designed a web-based pediatric ECG curriculum aimed specifically at PEM providers with the overall goal of improving the "first read" accuracy of ECG interpretation and to decrease the number of missed diagnoses. Based on learner feedback, we determined that the implementation of a combined module-based and didactic pediatric ECG curriculum improved the ability of PEM fellows to accurately interpret ECGs with abnormalities.